Oncostatin M Drives Th2 Polarized Allergic Airway Inflammation Through Fibroblast Reprogramming and Endoplasmic Reticulum Stress - Zhang H; Chen X; Liu L; Zheng H; Yang X; Yin K; Yao Q; Li L; Yang P (International Journal of Nanomedicine, 2025)
Huanping Zhang,1,* Xiaoxue Chen,1,* Le Liu,2 Haoyue Zheng,2 Xing Yang,1 Kai Yin,1 Qi Yao,1 Lei Li,1 Pingchang Yang2 1Department of Allergy Medicine, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, Tongji Shanxi Hospital, Third Hospital of Shanxi Medical University, Taiyuan, 030032, People’s Republic of China; 2State Key Laboratory of Respiratory Diseases Allergy Division at Shenzhen University and Institute of Allergy & Immunology, Shenzhen University School of Medicine, Shenzhen Key Laboratory of Allergy & Immunology, Shenzhen, People’s Republic of China*These authors contributed equally to this workCorrespondence: Pingchang Yang, Shenzhen University, Room A7-509, Lihu Campus, 1066 Xueyuan Blvd, Shenzhen, 518055, People’s Republic of China, Email pcy2356@163.comBackground: Allergic airway inflammation, characterized by Th2 cytokine production and eosinophilic infiltration, is a hallmark of asthma. The airway epithelium plays a pivotal role in orchestrating allergic responses by releasing cytokines such as oncostatin M (OSM). This study investigates the role of OSM in dust mite extract (DME)-induced allergic airway inflammation and identifies a novel mechanism by which OSM drives Th2-polarized inflammation.Methods: A murine model of DME-induced airway inflammation was established. Mice were treated with CelEd, a nanoparticle carrying fibroblast-targeting device and ATF4 siRNA.Results: We observed that DME exposure significantly upregulates OSM expression in airway epithelial cells, both at the mRNA and protein levels. This finding was corroborated in human bronchial epithelial cell lines, where DME exposure induced dose-dependent OSM secretion. Intranasal administration of OSM in naïve mice phenocopied the hallmark features of allergic inflammation, including eosinophilic infiltration and elevated Th2 cytokines, highlighting OSM’s sufficiency to drive allergic responses. Mechanistically, we discovered that OSM promotes IL-4 production through fibroblast reprogramming, involving endoplasmic reticulum stress (ERS) activation. OSM signaling in fibroblasts led to ERS and subsequent activation of the PERK-eIF2α-ATF4 pathway, which drives IL-4 transcription via the ATF4/Mef2d/GATA3 axis. Importantly, targeting this pathway through fibroblast-specific ATF4 knockdown significantly alleviated allergic pathology, including airway eosinophilia, Th2 cytokine production, and airway hyperresponsiveness.Conclusion: These findings underscore the critical role of OSM in allergic airway inflammation and identify the OSM-ERS-IL-4 axis as a potential therapeutic target for asthma and other allergic diseases. Keywords: Oncostatin M, OSM, endoplasmic reticulum stress, ERS, IL-4, airway fibroblasts, allergic airway inflammation